2017
DOI: 10.1111/acel.12689
|View full text |Cite
|
Sign up to set email alerts
|

TOR‐mediated regulation of metabolism in aging

Abstract: SummaryCellular metabolism is regulated by the mTOR kinase, a key component of the molecular nutrient sensor pathway that plays a central role in cellular survival and aging. The mTOR pathway promotes protein and lipid synthesis and inhibits autophagy, a process known for its contribution to longevity in several model organisms. The nutrient‐sensing pathway is regulated at the lysosomal membrane by a number of proteins for which deficiency triggers widespread aging phenotypes in tested animal models. In respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 236 publications
(280 reference statements)
1
92
0
Order By: Relevance
“…Changes in nutritional and epigenetic state are integral to aging. This can be judged by the central role of the mTOR pathway [ 9,10 ] and histone/DNA methylation [ 58,59 ] in organismal aging. αKG has emerged as master regulatory metabolite in aging biology as it is a key TCA intermediate, a cofactor for numerous transamination reactions, [ 60,61 ] a cofactor for the prolyl hydroxylase dependent hydroxylation of the transcription factor hypoxia inducible factor‐1 (HIF‐1) [ 62–64 ] and a cofactor for epigenetic enzymes, histone, and DNA demethylases.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…Changes in nutritional and epigenetic state are integral to aging. This can be judged by the central role of the mTOR pathway [ 9,10 ] and histone/DNA methylation [ 58,59 ] in organismal aging. αKG has emerged as master regulatory metabolite in aging biology as it is a key TCA intermediate, a cofactor for numerous transamination reactions, [ 60,61 ] a cofactor for the prolyl hydroxylase dependent hydroxylation of the transcription factor hypoxia inducible factor‐1 (HIF‐1) [ 62–64 ] and a cofactor for epigenetic enzymes, histone, and DNA demethylases.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…This line of inquiry was prompted by the knowledge that treatments known to extend lifespan in various organisms (e.g. TOR inhibition and calorie restriction) lead to Maf1-dependent repression [11,14,43] while deletion of Maf1 in yeast reduces chronological lifespan [42,44]. The tm6082 allele removes the phylogenetically conserved box C region, including three of the four β-sheets that make up the central core of Maf1 along with additional sequences (a total of 79 amino acids) and introduces 37 different amino acids in their place [42,45,46].…”
Section: Impact Of Maf1 On Cell Physiology In Metazoansmentioning
confidence: 99%
“…On the contrary, mTORC2 mainly serves to control cell survival and proliferation, via activating the Akt pathway (Zoncu, Efeyan & Sabatini, 2011). On the basis of its pro‐anabolic capability and central role in governing metabolic homeostasis, numerous evidence has demonstrated that inhibition of mTOR activity could lead to extended lifespan among mammalian species, implying a direct link between mTOR pathway and aging (Antikainen, Driscoll, Haspel, & Dobrowolski, 2017). Regarding the pathophysiological association between aging and Alzheimer's disease, the impact of mTOR in Alzheimer's disease has therefore been extensively investigated.…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Amentioning
confidence: 99%